Environmental impact on biochemical parameters during developmental stages of Citrus fruit - Kumar, Dinesh; Ram, Lallan; Ladaniya, M. S.; Khadse, Archana; Kumar, Sunil (Indian Journal of Horticulture, 2019)
Influence of climate (temperature and rainfall) on biochemical and antioxidant capacity of Nagpur mandarin (Citrus reticulata Blanco) fruit was studied during the two consecutive years. At fruit maturity stage higher vitamin C was recorded as 36.49mg/100ml at minimum temperature level at location 2 and total soluble solid contents was found to be 8.28°B at fruit maturity stage at location 1. Pectin estimated as calcium pectate was recorded as 2.76% in the fruit peel and 1.16% in the fruit juice in the maturity stage at location 1. PME activity was found higher (4.21 U/ml) in the mature fruit juice of Nagpur mandarin at location 1. Total phenol and total flavonoid content were recorded as 7.35 mg/100ml and 8.16 mg/lit respectively in fruit juice at location 1. The findings indicated that varies temperature and rainfall pattern at a moderate rainfall zone (Nagpur district referred as location 1) significantly influence the biochemical parameters and antioxidant activity in Indian citrus (Citrus reticulata Blanco) at maturity stage.